Rethinking Profit: How Redistribution Drives Growth - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2014)
Using a combination of heterodox economics and biophysical analysis, this paper investigates the relationship between economic distribution and the growth of material throughput. Empirical results show that the growth of “useful work” correlates with redistribution towards profit. Furthermore, increases in energy consumption are correlated with increases in the largest corporations' share of total employment. These results are synthesized to form a new theory linking profit, social hierarchy, and growth.
Keywords: 330; economic growth; social hierarchy; profit; redistribution